Distribution of Cognitive Levels Analysis in Reading Exercises of English for Nusantara Textbook - Agesti, Ervinda; Kholid, M. Ridho; Suryawati, Sri Suci (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
Reading exercises in textbooks play an important role in shaping students’ cognitive experiences, particularly in English language learning. However, the levels of cognitive processes required by textbook reading exercises need to be systematically analyzed to identify the cognitive orientation being developed. This study aims to analyze the distribution of cognitive process levels in reading exercises in the English for Nusantara Grade VIII textbook based on the Revised Bloom’s Taxonomy framework. This study employed a qualitative descriptive approach using content analysis techniques. The data consisted of reading tasks found in the textbook, with a total of 140 tasks identified. Seventeen tasks were excluded because they did not meet the criteria of the Cognitive Process Dimension (CPD), resulting in 123 specific reading tasks being analyzed. Each task was classified into the six levels of cognitive processes in the Revised Bloom’s Taxonomy through verbatim tabulation and theory-based judgment, which were verified through expert judgment by English teachers. The results indicate that the distribution of cognitive process levels is dominated by Remembering (43.09%) and Understanding (36.59%). Applying (2.44%), Analyzing (10.57%), and Evaluating (7.32%) appear in smaller proportions, while no reading tasks were found at the Creating level (0.00%). In conclusion, the reading exercises in the English for Nusantara Grade VIII textbook are oriented toward low- to mid-level cognitive processes, with limited opportunities for the development of higher-order thinking skills. Therefore, more cognitively balanced reading exercises are needed to optimize the role of reading activities in learning.